Crystal structure of 2-(thiazol-2-yl)hexahydro-1H-4,7-epoxyisoindole-1,3(2H)-dione, C11H10N2O3S - Wang Qinglong; Hou Xuehui (Zeitschrift für Kristallographie - New Crystal Structures)
C11H10N2O3S, monoclinic, Cm (no. 8), a = 10.8483(7) Å, b = 9.3377(8) Å, c = 5.4086(3) Å, β = 95.398(6)°, V = 545.45(7) Å3, Z = 2, Rgt (F) = 0.0576, wRref (F 2) = 0.1429, T = 293(2) K.